Creative Cardiff: Utilising cultural mapping for community engagement. (December 2017) - Murray, Samuel
Abstract: In 2014 Cardiff University set up a Creative Economy team tasked with exploring how the university could improve its relationship with creative practitioners around the city. To explore this relationship the team embarked upon a research project to map creative industries in the city using a mixed methodology of online data collection and semi-ethnographic interviews. As the project progressed the creative economy team designed and launched a city-wide creative network Creative Cardiff connecting the city's creative populous through events, resources and a website with membership subscription. This article explores how mapping can be used to develop the university/creative economy relationship within metropolitan spaces as a contributor to the development of the modern civic university. It also explores the opportunities and challenges posed by a mapping project of this scale, taking into account debates in cultural mapping literature as to what a map actually is. Highlights: Mapping the creative economy in Cardiff has paved the way for work to build a creative hub, the data will feed into its location and requirements. Mapping the creative economy of Cardiff allows the university to see how it could plan future investment in creative courses. For freelancers in every Cardiff postcode Music, Performing & Visual arts is the largest sector. For organisations Music, Performing and Visual Arts is the largest sector in all Cardiff postcodes except CF14 & CF3 and CF64. Challenges remain in identifying the number of creative individuals who work within organisations and how to reach those without internet presence.